Optimalisasi Penerimaan Pajak Melalui Kegiatan Forensik Digital Untuk Tujuan Perpajakan - Nugroho, Panji Wisnu; Liyana, Nur Farida (Politeknik Keuangan Negara STAN, 2024)
This research aims to review the implementation of digital forensic activities and their impact on tax revenue at the Directorate General of Taxes (DGT), especially in South Jakarta I Regional Tax Office. This study details the research methods used, including literature review methods to understand the overview of digital forensic activity implementation, and field research methods through interviews with Digital Forensic Expert and academics experienced in tax law enforcement processes. The research results indicate that the implementation of digital forensic activities has been carried out in accordance with applicable Standard Operating Procedures. However, digital forensic activities have not yet had a significant impact on tax revenue. There are several obstacles faced in the digital forensic business process, such as the limited number of Digital Forensic Experts in DGT, uneven human resource capabilities, and limited availability of supporting devices. Therefore, this research is expected to serve as a guide for policymakers to optimize state revenue through increased effectiveness in law enforcement, especially those related to digital forensic activities.